Servitude of transmission - restriction of exercise of ownership right? - Westfal, Krzysztof (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The study aims at an analysis of the servitude of transmission as a form of restriction of the ownership. The author is contrasting the legal status of landlords from the times before servitude of transmission was established and after its implementation. The author is of the opinion that taking into consideration the vast range of powers the landlords have today, servitude of transmission may be treated as, at least, a favorable adjustment.